Court-ordered inpatient psychiatric care in Switzerland: determinants of length of stay and treatment outcome - Weber, Kerstin; Morier, Sandrine; Lesaffre, Lise; Menu, Christophe; Bertschy, Philippe; Herrmann, François R.; Giannakopoulos, Panteleimon (Frontiers in Psychiatry, 2023)
In several European countries, offenders with decreased or abolished responsibility and high risk of recidivism due to long-lasting mental disorders are compulsory admitted for courtordered treatments (COT) that take place in high and medium-security hospitals. As a rule, length of stay in these structures is very long implying major restrictions for the inmate and high societal cost. Despite intensive research, the predictors of length of stay and treatment outcome in long stay forensic services is still matter of debate. We report here a detailed analysis of the demographic, psychiatric and offense predictors of length of stay and discharge locations of 204 mentally disordered offenders convicted to COT in a new medium-security forensic psychiatry clinic in Geneva, Switzerland. Kaplan-Meier survival estimates were performed to determine time to release. Length of stay was predicted by Cox regressions, and discharge locations were predicted by multinomial logistic regressions. The typical inpatient was a 35-age single male re-offender, submitted to COT after a conviction for physical violence (78.9%) or property violation (64.2%), with drug trafficking (52.9%), in relation to psychotic (67.2%), antisocial or borderline personality disorder (35.8%) with comorbid substance use disorders (60.3%). Sex offenses were found in 24.5% of cases and were associated with Cluster B personality disorders. The median length of stay was of 2.5 years and was independent of demographic variables, severity of crime recidivism and psychiatric diagnosis. Longer COT at admission, and type of offense (in particular drug traffic and sexual violence) predicted longer stays. At discharge, 32.8% of cases were transferred to sheltered educational housing, 23.1% to open low-security wards, while 30.6% returned to regular prisons and 9.7% to their country of origin. Younger age and conviction for property violation rather than physical violence increased the chances to be discharged to sheltered educational housing. Longer COT at admission, personality disorders, and conviction for sexual offense increased the risk to return to prison. These data suggest that sex offenses determine not only longer stays under COT but also drastically decreases the chance of freedom for inmates with Cluster B personality disorders. * p<0.05, ** p<0.01